Wildlife Victims in the Gaurishankar Conservation Area - Karki, Sujata (Patan Prospective Journal, 2023)
Human-wildlife conflict is a major conservation challenge in Nepal, particularly in the Gaurishankar Conservation Area. This study examines the status of Human-Wildlife Conflict in Gaurishankar Conservation Area focusing on fieldwork in Lamabagar, ward no-1, Dolkha district, Nepal. It aims to identify the stress experienced by wildlife victims, analyzing their problems from social work and stress coping perspectives. The research utilizes qualitative and quantitative methods for data collection and analysis, addressing a notable gap in literature regarding social work perspectives on human-wildlife conflict. The study aims to estimate the stress levels resulting from human-wildlife conflict. This stress, when unmanaged, poses mental health challenges. Animals like monkeys, porcupines, gorals, deer, and Himalayan black bears impact community livelihoods by damaging crops and posing a threat to humans. In the research primary and secondary data has been used. Analyzing the data is supposed to lead to a conclusion.